Analisis Safety Management System Petugas AMC Dalam Menangani Bahaya Hewan Liar di Area Airside Bandar Udara Adi Soemarmo Surakarta - Sulthan Abdi Rahman Mafaza; Eny Sri Haryati (Jurnal Multidisiplin Madani, 2022)
The role of airports in the transportation network has a very important function in the transportation system. When viewed from an economic point of view, the role of airports in the transportation system uses suppliers (providers of goods), manufactures and consumers so as to create a pattern that is productive and efficient and is a major factor in economic development. PT. Angkasa Pura I Adi Soemarmo Surakarta has a goal that can support improving the quality and quality of airport services, one of which is to become a commercial airport that is able to provide airport services, in accordance with established international standards and is able to meet the needs of service users. This study aims to determine the application of the safety management system of AMC officers in dealing with wild life hazard management in the airside area of Adi Soemarmo Airport, Surakarta. Knowing solutions that can be applied to problems regarding wildlife hazard management and handling wild animals in the airside area of Adi Soemarmo Airport, Surakarta. The researcher used triangulation technique as a technique to check the validity of the data. According to Sugiyono (2019) in data collection techniques, triangulation is defined as a data collection technique that combines various data collection techniques and existing data sources. Based on the results of research conducted at Adi Soemarmo Airport, Surakarta regarding the analysis of the safety management system of AMC officers in dealing with the dangers of wild animals that have been carried out by AMC officers in the airside area, it is in accordance with procedures and carried out carefully, this is evidenced by the results of their work and efforts in handling wild animals that interfere with the activities of workers in the airside area.